The effect of feeding medium chain fatty acids (MCFA) on nursery pig growth in an attempt to replace ZnO or carbadox - Lawrence, Jaymi M.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
Due to high demands from consumers to limit antimicrobial usage in nursery pig diets, pork producers are seeking antimicrobial replacements that improve growth performance. Literature suggests a possible replacement to dietary antimicrobials could be medium chain fatty acids (MCFA). However, only limited data about the efficacy of MCFA exists and very few studies compare MCFA to other antimicrobials like ZnO or carbadox. Therefore, the objective of this study was to evaluate the effects of feeding MCFA, ZnO and carbadox on weanling growth performance. A total of 360 weanling pigs (DNA 200×400;5.4±0.06 kg;) were used in a 35-d experiment with 6 pigs/pen and 10 pens/treatment. There were 6 treatments: 1) negative control; 2) ZnO (3,000 ppm in phase 1 and 1,500 ppm in phase 2); 3) carbadox (50 g/ton); 4) 1% C6:C8:C10 (MCFA blend); 5) 1% R2 (Feed Energy, City, IA); 6) 1% FORMI GML (ADDCON; Bitterfeld-Wolfen, Germany). Pens were allotted to treatments in a completely randomized design. Pig and feeder weights were collected weekly. Data was analyzed using PROC GLIMMIX (SAS version 9.4; Cary NC). Treatment diets were fed in two phases from weaning to d 19 of the experiment. A common phase 3 diet was fed from d 20 to 35. During the first phase, pigs fed ZnO or carbadox had improved (P< 0.05) ADG compared to control or R2 diets. For pigs fed ZnO compared to pigs fed the negative control ADFI was improved (P <0.05) with little impact on G:F (P <0.078). It can be concluded that ZnO and carbadox improved weanling growth and feed intake while MCFA were variable in performance. Therefore, further research on the feasibility of feeding MCFA in place of ZnO or other antimicrobials is needed.
Keywords: Spring 2019